Escuela de Liberales: El Período de Las Cortes de Cádiz en los manuales escolares peruanos (2010 Y 2017) - Parodi Revoredo, Daniel (2020)
This investigation research the presence of nationalist ideology and the values of republicanism and political liberalism in school textbooks published in Peru, between 2010 and 2017, when dealing with the period of Las Cortes de Cádiz (1808-1815). From the critical discourse analysis (ACD)approach, and taking into account the National Curricular Design of Regular Basic Education, both the stories and the didactic activities of the manuals are analyzed, a diagnosis is established and some alternatives are offered to reinforce citizens competences to through the teaching of this historical period. This work is original because it applies the ACD to the contents of the history textbooks, because it investigates the development of citizen skills in its pages and because the historians interested in these manuals have not focused their attention on the subject period of this study.